Constitution as a legal instrument of society: issues and trends - L YU Grudtsina; A V Lagutkin (RUDN Journal of Law, 2015)
In the article there is an attempt to understand, taking into account the historical experience, the social, legal and economic nature of the Constitution as a legal management tool, issued in the end of the XVIII century, which has a dual nature. On the one hand, the historical appearance of the Constitution as a legal act related to the socio-economic (structural public) shifts (revolutions) in developing societies, when the Constitutions replaced the monarchs and were a tool of society, which was negotiating with the state. On the other hand, the evolution of the spirit of the Constitution over the past two centuries almost completely changed its content, when it is not society dictates its terms to the state, but the state with the help of the Constitution establishes for the society those or other requirements, obligations, legal boundaries. From the subject of management society is transformed into an object of management, and the state, which once acted as a control object, becomes the subject of management. In this regard, according to the authors, it is necessary to consider the suitability of this instrument of management (Constitution) to the changing realities. Social Contract may become a desired national idea of Russia, uniting the state and society and contributing to the development of democracy at its best.